MITIGASI RISIKO PEKERJAAN PROYEK KONSTRUKSI BANGUNAN GEDUNG LOBBY DAN RENOVASI FASAD TK DWIJENDRA DENPASAR - Ni Putu Yunita Laura Vianthi; Arya Bagus Mahadwijati Wijaatmaja; Desak Made Sukma Widiyani; Anak Agung Ayu Sri Ratih Yulianasari (Universitas Dwijendra, 2024)
This article discusses risk mitigation in the construction project of the lobby building and facade renovation of TK Dwijendra Denpasar. In this project, risk identification is crucial to understand the potential risks of each activity and then analyze the impact on the continuity of the construction project. The author successfully identified as many as 81 risks from 11 possible risk sources in this project. To reduce the negative impact of the identified risks, the author suggests several risk mitigation strategies, such as retaining risk, reducing risk, transferring risk, and avoiding risk. These strategies can help manage uncertainties related to potential hazards in construction projects.